UPAYA PENINGKATAN KEHADIRAN SISWA MELALUI HOME VISIT DAN PENDEKATAN PERSONAL DALAM KEGIATAN PPK DI MA AL-MUHDI - Miswan Ramdani; Dede Hermansyah; Delis Adinda Bilqis; Muhammad Abdul Aziz (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student attendance constitutes a fundamental indicator of instructional continuity and character development in madrasah education. Irregular and low attendance rates remain evident at Madrasah Aliyah Al-Muhdi, thus requiring systematic educational interventions involving both teachers and parents. This study aims to analyze the initial condition of student attendance, the implementation of the home visit program, the forms of teachers’ personal approaches, and the effectiveness of these strategies in improving student attendance during the Teaching Practice (PPK) program. This research employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing with triangulation techniques. The findings reveal that the home visit program strengthened school–family partnerships and increased parental involvement in monitoring students’ learning. Teachers’ personal approaches, implemented through individualized guidance and interpersonal communication, improved students’ motivation and discipline awareness. Overall, these strategies significantly enhanced student attendance and consistency.